The effect of different mouthwashes on bacteremia after debonding - Akbulut, Y. (Wolters Kluwer Medknow Publications, 2020)
Objectives: This study aims to investigate the effects of various mouthwashes on bacteremia development following a debonding process, which is performed after orthodontic treatment. Subjects and Methods: The study included patients who received fixed orthodontic treatment and were indicated for debonding. A total of 40 patients in four groups were selected for the study; no mouthwash (Group 1), mouthwash containing 0.12% chlorhexidine-gluconate (Group 2), mouthwash containing essential-oils (Group 3), and mouthwash containing 7.5% povidone-iodine (Group 4). Before (T0) and following (T1) the debonding procedure, blood samples were obtained from the patients. Then, the blood samples were placed in blood culture bottles to investigate bacterial growth. Results: Based on the results of the study, it was determined that the blood samples obtained at T0did not indicate any bacterial growth. Furthermore, it was observed that the blood samples obtained at T1included Streptococcus viridans, Streptococcus oralis, Streptococcus mutans, and Staphylococcus aereus growth, respectively, in 4 patients from Group 1 while Streptococcus salivarius growth was observed in 1 patient from Group 3 in addition to Streptococcus mitis growth in 1 patient from Group 4. No bacterial growth was observed in Group 2. While the results obtained between Group 1 and Group 2 were statistically significant, no statistically significant difference was observed between other groups. Conclusions: Finally, it was determined that the mouthwash 0.12% chlorhexidine-gluconate was statistically significant in comparison to the control group. It can be concluded that this mouthwash can be used to decrease bacterial density in oral flora before debonding procedures.
Keywords: Bacteremia; bacterial endocarditis; chlorhexidine gluconate; debonding; mouthwashes